Simultaneous detection and partial molecular characterization of five RNA viruses associated with enteric disease in chickens: chicken astrovirus, avian nephritis virus, infectious bronchitis virus, avian rotavirus a and avian orthoreovirus, via multiplex RT–qPCR - Loor-Giler, Anthony; Muslin, Claire; Santander-Parra, Silvana; Coello, Dayana; Robayo-Chico, Marcela; Ferreira, Antonio Piantino; Nunez, Luis (Frontiers in Veterinary Science, 2025)
In the poultry industry, intestinal diseases can lead to significant economic losses due to diarrhea, weight loss and mortality, often linked to viral infections. Chicken astrovirus (CAstV), avian nephritis virus (ANV), infection bronchitis virus (IBV), avian rotavirus A (AvRVA) and avian orthoreovirus (ARV) are key pathogens on this disease including feed malabsorption and runting-stunting syndrome (RSS). This study proposes a multiplex RT–qPCR assay for the simultaneous detection of these five viruses in chickens with enteritis in Ecuador. Primers and hydrolysis probes were designed for the five viruses, along with a synthetic gBlock as a positive control. The method was evaluated for sensitivity, repeatability, and specificity, and 200 jejunal samples were tested. Genome regions of each virus were sequenced, and a phylogenetic analysis confirmed their presence in the samples. The optimized RT-qPCR assay showed efficiency between 98.8–105.9%, with a detection limit of 1 copy/μL. It specifically amplified the five target viruses without cross-reactivity. Among 200 chickens tested, 97% were positive for at least one virus, with ANV (89%) and CAstV (53%) being the most prevalent. Coinfections were common, especially between CAstV and ANV, with three samples positive for all viruses. Sequencing and phylogenetic analysis confirmed the circulation of multiple strains in chickens with enteric disease in Ecuador. This study describes a multiplex RT-qPCR assay for detecting key enteric viruses in Ecuadorian poultry highlighting the high prevalence of astroviruses, emphasizing the impact of coinfections, its possible role in the disease and the importance of improving disease control strategies.